ISO 9001 certification and service quality delivery in Malaysian higher education institutions: A conceptual model - Rahmisafa, Hamid; Hasmadi, Hassan; Muzafar, Mat Yusof (Universiti Malaysia Pahang, 2021)
In line with the strategies for accelerating the achievement of quality education, ISO 9001 Quality Management System (ISO 9001) was introduced as a mean to enhancing performance and effectiveness of the Malaysian HEIs’ delivery systems. The key objective for which the HEIs adapting ISO 9001 to practice rests on the premise that the certification able to establish continuity in management procedures which then contributing to betterment performance. Adoption the certification in the education sector is, however, relatively new and has yet to be understood clearly. Indeed, the limited literature surrounding ISO 9001 in education indicates the effectiveness of the certification is vague and inconclusive. Given the literature gap, this paper presents a conceptual model on the link between ISO 9001 and performance outcomes. Since the primary focus of ISO 9001 is to meet customer requirements, the performance outcomes are measured by service quality delivered by the HEIs. The model depicts that successful implementation of ISO 9001 depends upon its seven quality management principles including customer focus, leadership, engagement of people, process approach, improvement, evidence-based decision making, and relationship management. Meanwhile, the outcomes of the certification are expected to enhance customer satisfaction, depend upon the perceived service quality delivery, measured by SERVPERF scale consisting of five dimensions including academic aspects, non-academic aspects, reputation, access, and program issues. It should be noted that the presented model is a tentative one and will undoubtedly need to be verified and validated in the next stage of research. Therefore, the model is conceptual in nature and will be validated in further research